A discriminative test among the different theories proposed to explain the origin of the genetic code: The coevolution theory finds additional support. (July 2018) - Di Giulio, Massimo
Abstract: A discriminative statistical test among the different theories proposed to explain the origin of the genetic code is presented. Gathering the amino acids into polarity and biosynthetic classes that are the first expression of the physicochemical theory of the origin of the genetic code and the second expression of the coevolution theory, these classes are utilized in the Fisher's exact test to establish their significance within the genetic code table. Linking to the rows and columns of the genetic code of probabilities that express the statistical significance of these classes, I have finally been in the condition to be able to calculate a χ 2 value to link to both the physicochemical theory and to the coevolution theory that would express the corroboration level referred to these theories. The comparison between these two χ 2 values showed that the coevolution theory is able to explain – in this strictly empirical analysis – the origin of the genetic code better than that of the physicochemical theory.